Clinic Versus Ambulatory Blood Pressure in Resistant Hypertension: Impact of Antihypertensive Medication Nonadherence. Issue 5 (November 2019) - Hamdidouche, Idir; Gosse, Philippe; Cremer, Antoine; Lorthioir, Aurelien; Delsart, Pascal; Courand, Pierre-Yves; Denolle, Thierry; Halimi, Jean-Michel; Girerd, Xavier; Ormezzano, Olivier; Rossignol, Patrick; Pereira, Helena; et al.
Abstract : Clinic-ambulatory blood pressure (BP) difference is influenced by patients- and device-related factors and inadequate clinic-BP measurement. We investigated whether nonadherence to antihypertensive medications may also influence this difference in a post hoc analysis of the DENERHTN trial (Renal Denervation for Hypertension). We pooled the data of 77 out of 106 evaluable patients with apparent resistant hypertension who received a standardized antihypertensive treatment and had both ambulatory BP and drug-screening results available at baseline after 1 month of standardized triple therapy and at 6 months on a median of 5 antihypertensive drugs. After drug assay samplings on study visits, patients took their antihypertensive treatment under supervision immediately after the start of the ambulatory BP recording, and supine clinic BP was measured 24 hours post-dosing; both allowed to calculate the clinic minus daytime ambulatory systolic BP (SBP) difference (clinic-SBP–day-SBP). A total of 29 (37.7%) were found nonadherent to medications at baseline and 38 (49.4%) at 6 months. At baseline, the mean clinic-SBP–day-SBP difference in the nonadherent group was 12.7 mm Hg (95% CI, 7.8–17.7 mm Hg, P <0.001). In contrast, clinic SBP was almost identical to day-SBP in the adherent group (clinic-SBP–day-SBP difference, 0.1 mm Hg; 95% CI, −3.3 to 3.5 mm Hg; P =0.947). Similar observations were made at 6 months. Using receiver operating characteristics curves, we found that a 6 mm Hg cutoff of clinic-SBP–day-SBP difference had 67% sensitivity and 69% specificity to predict nonadherence to the triple therapy at baseline. In conclusion, a large clinic-SBP–day-SBP difference may help discriminating between adherence and nonadherence to treatment in patients with resistant hypertension. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01570777.